Analisis Isi Pemberitaan Brand KFC di Media Daring dan Pengaruhnya terhadap Reputasi Brand pada Bulan Maret- April 2023 - Shadrina Anwar, Adani Nur (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study analyzes the coverage of the KFC brand in online media during the period of March-April 2023 and its impact on the brand's reputation. Using a literature study method and the Brand24 analytical tool, the study collected and analyzed data from various online news portals. The findings show that during this period, there were 885 mentions of KFC, with 87% positive sentiment and 13% negative sentiment. Positive coverage was mainly related to restaurant promotions, cooking recipes, and Ramadan sales ideas, which helped enhance brand image and awareness. Conversely, negative coverage was related to specific incidents that could affect public perception of the brand. This study highlights the importance of reputation management in the digital era and the significant impact of media coverage on brand image.